Preparation gold nanoparticles using herb leaf extract for electro-oxidation determination of ascorbic acid. Issue 9 (2nd September 2018) - Zheng, Yuhong; Zhang, Huaiwei; Fu, Li
Abstract: Green and efficient synthetic methods have been gaining great interest for the preparation of nanoparticles. In this contribution, the biosynthesis of gold nanoparticles (Au NPs) and its electro-oxidation activity for determination of ascorbic acid was studied. The biosynthesis of Au NPs was carried out using the Plectranthus amboinicus leaf extract as reducing agent and stabilizer. The optical property of biosynthesized Au NPs was determined by UV–Vis spectrophotometer. We further investigated the electro-catalytic property of the biosynthesized Au NPs by electro-oxidation of ascorbic acid.